Faster road racing 5K to half marathon - Pfitzinger, Pete 1957-; Latter, Philip 1981- (Human Kinetics, 2015)
A training guide that covers the most popular race distance, including the 5K, 10K and half marathon. It contains detailed plans for specific distances as well as expert advice on balancing training and recovery, cross-training, nutrition, tapering and training beyond the age 40